The Effect of Characteristics, Patient Knowledge and Availability of Pulmonary TB Drugs with Compliance with Taking Pulmonary TB Drugs at the Jambi City Health Center in 2023 - Hisran Hisran; Sugiarti Sugiarti; Helmi Suryani Nasution; Vinna Rahayu Ningsih (Eduvest - Journal of Universal Studies, 2024)
Tuberculosis (TB) is a disease caused by *Mycobacterium tuberculosis*. One of the factors contributing to the low cure rate is non-adherence to TB treatment. Non-adherence is influenced by patient-related factors, including respondent characteristics, knowledge about pulmonary TB, and drug availability. The objective of this study is to analyze the influence of respondent characteristics, namely age, gender, education, knowledge about pulmonary TB, and drug availability on adherence to medication. This is a quantitative study with a cross-sectional approach. Samples were collected proportionally from 59 pulmonary TB patients undergoing treatment at 20 community health centers. The instrument used was a questionnaire based on MMAS-8, and the data were analyzed using univariate and bivariate analyses with Spearman Rho correlation test and Ordinal Logistic Regression. Adherence to pulmonary TB treatment was better in the older age group (36-45 years) with 85.4%, those with a high school education at 73.2%, respondents with high knowledge at 63.4%, and those reporting good drug availability at 88.9%. No respondents were categorized as non-adherent. The factors significantly affecting adherence to TB treatment were age (p = 0.046), education level (p = 0.013), knowledge (p = 0.021), and drug availability (p = 0.000), with drug availability having the greatest influence. Meanwhile, gender did not have a significant effect on adherence. The R-Square value was 0.525, and the regression equation was \( Y = 0.492 + 0.190 X1 – 0.101 X2 + 0.195 X3 + 0.356 X4 + 0.505 X5 + ε \).